Baseline Muscle Mass Is a Poor Predictor of Functional Overload-Induced Gain in the Mouse Model - Kilikevicius, Audrius; Bunger, Lutz; Lionikas, Arimantas (Frontiers in Physiology, 2016)
Genetic background contributes substantially to individual variability in muscle mass. Muscle hypertrophy in response to resistance training can also vary extensively. However, it is less clear if muscle mass at baseline is predictive of the hypertrophic response. The aim of this study was to examine the effect of genetic background on variability in muscle mass at baseline and in the adaptive response of the mouse fast- and slow-twitch muscles to overload. Males of eight laboratory mouse strains: C57BL/6J (B6, n=17), BALB/cByJ (n=7), DBA/2J (D2, n=12), B6.A-(rs3676616-D10Utsw1)/Kjn (B6.A, n=9), C57BL/6J-Chr10A/J/NaJ (B6.A10, n=8), BEH+/+ (n=11), BEH (n=12) and DUHi (n=12), were studied. Compensatory growth of soleus and plantaris muscles was triggered by a 4-week overload induced by synergist unilateral ablation. Muscle weight in the control leg (baseline) varied from 5.2±07 mg soleus and 11.4±1.3 mg plantaris in D2 mice to 18.0±1.7 mg soleus in DUHi and 43.7±2.6 mg plantaris in BEH (p<0.001 for both muscles). In addition, soleus in the B6.A10 strain was 40% larger (p<0.001) compared to the B6. Functional overload increased muscle weight, however, the extent of gain was strain-dependent for both soleus (p<0.01) and plantaris (p<0.02) even after accounting for the baseline differences. For the soleus muscle, the BEH strain emerged as the least responsive, with a 1.3-fold increase, compared to a 1.7-fold gain in the most responsive D2 strain, and there was no difference in the gain between the B6.A10 and B6 strains. The BEH strain appeared the least responsive in the gain of plantaris as well, 1.3-fold, compared to 1.5-fold gain in the remaining strains. We conclude that variation in muscle mass at baseline is not a reliable predictor of that in the overload-induced gain. This suggests that a different set of genes influence variability in muscle mass acquired in the process of normal development, growth and maintenance, and in the process of adaptive growth of the muscle challenged by overload.